2014 International Wireless Communications and Mobile Computing Conference (IWCMC) 2014
DOI: 10.1109/iwcmc.2014.6906470
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating snort NIDS using NetFPGA-based Bloom filter

Abstract: In recent years, network intrusion detection systems (NIDS) have faced a serious throughput challenge as a result of the rapid increase of network links to 1 and 10 Gbps rates. Consequently, this calls for NIDS to have wire-speed packet processing and real-time detection of malicious traffic. Snort is the most popular NIDS. Snort is an open source software-based NIDS and runs as a single threaded application. Snort processing and detection capabilities can be limited in networks with 1 and 10 Gbps network link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Software DPIs (such as SNORT, Bro, and L7-filter) are detailed described in [29]. For a pattern matching algorithm used in DPI there are two categories: software (KMP [18], BM [20], AC [21] and WM [22]) and hardware (DFA [23], BF [24,25], and CAM). Pattern matching described in [26] is capable of operating at 8Gbps.…”
Section: B Payload Processing Design Of Netfpga-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…Software DPIs (such as SNORT, Bro, and L7-filter) are detailed described in [29]. For a pattern matching algorithm used in DPI there are two categories: software (KMP [18], BM [20], AC [21] and WM [22]) and hardware (DFA [23], BF [24,25], and CAM). Pattern matching described in [26] is capable of operating at 8Gbps.…”
Section: B Payload Processing Design Of Netfpga-basedmentioning
confidence: 99%
“…Simultaneously, in paper [43] gave a comparison between them. Furthermore, to prevent degrading network throughput in detecting strings in streaming data, a data structure Bloom Filter [24,25] is used in DPI. The storage needed by Bloom Filter is always dependent of string's length.…”
Section: B Payload Processing Design Of Netfpga-basedmentioning
confidence: 99%
“…Acharya et al [17] studied and analysed the functionality of network firewalls to enhance its performance by modifying rule orders dynamically based on the incoming traffic characteristics. Similarly, for Snort IDS, ample recent research work has been reported in the literature [18][19][20][21][22] to enhance the performance of Snort IDS using hardware-assisted techniques such as FPGA, GPU and multi-core processors. The idea in most of these techniques is to offload the computation of Snort to hardware in order to obtain considerable speedup in performance.…”
Section: Related Workmentioning
confidence: 99%
“…Software‐based systems can only perform a limited number of operations and could not fulfill wire‐speed detection requirements. However, there are improvements in these systems, specifically the open‐source network intrusion detection system to provide fast detection .…”
Section: Introductionmentioning
confidence: 99%